AN INVESTIGATION OF THE STUDENTS' ABILITY AND DIFFICULTIES IN WRITING A NARRATIVE TEXT; A CASE STUDY OF THE FIRST GRADERS OF SENIOR HIGH SCHOOL - Luthfiyatun Thoyyibah, - (2010)
This study investigates ability and difficulties of senior high school students in writing a narrative text. The participants of this study were one teacher and a class of first graders in one senior high school in Cimahi. This study uses a qualitative approach, particularly case study. Data were collected from nine students' texts of different levels of achievement (low, mid, and high) and interview with both the teacher and the students. The data from students' texts were analyzed qualitatively in terms of the schematic structure and linguistic features using systemic functional grammar. The data from interview were also analyzed qualitatively relevant to the texts analyzed. Meanwhile, data from students' texts and interview were interpreted and classified in order to answer the research questions. The study reveals that the students' ability in terms of schematic structure and linguistic features of the low, mid and high achievers still needs improvement. The results show, in general those students from three different achievements have difficulties in subject-verb agreement, differentiating each schematic structure of a narrative and arranging ideas. Those results were supported by the data from the interview. Revealed that the teacher did not implement the genre based approach appropriately. Even though the teacher did not implement the GBA appropriately, there were some stages like in the GBA which help the students understand about writing a narrative. For practical purposes, it is recommended that English teachers should build knowledge of the field, give more models of the texts, be a good model for the students and give more time for students to write their own text. It is suggested that further study on students' ability and teaching and learning activities in writing class should be conducted in wider scope and contexts involving more participants and more in depth analyses of students' texts.